Class AK-manifold of Concircular curvature tensor (V) - Yaseen K. Abass; A. A. Shihab (Tikrit Journal of Pure Science, 2023)
The current deals with new Three classes of almost Kahler manifold W2 of Concircular curvature tensor are Calculating differential geometrical but also topological parameters appropriate for new classes 1, 2, and 3, are the  focus of the paper. Through it, an equivalence relationship was obtained between these classes and one of or more the Tensor compound in the  adjoint G-structure space and then construct a relation between this new classes.